Old Bug—New Challenges After COVID-19 Pandemic: Severe Invasive Streptococcus pyogenes Infections in Adults—A Single-Center Experience in Poland - Patrycja Leśnik; Jarosław Janc; Martyna Biała; Marzenna Bartoszewicz; Lidia Łysenko; Natalia Słabisz (Pathogens)
Since the beginning of December 2022, an unusually high number of cases and deaths of Group A Streptococcus (GAS) infections has been reported in many European countries. GAS infection frequently causes mild diseases such as pharyngitis, tonsillitis, impetigo, cellulitis, and scarlet fever. However, in rare instances, GAS infection can lead to invasive, life-threatening conditions like necrotizing fasciitis and toxic shock syndrome, which are associated with high mortality. The aim of the study was to present the clinical course of invasive Streptococcus pyogenes infections and to highlight the increase in the incidence of severe infections of this etiology, similar to trends observed in other European countries. The study included 11 patients with severe, invasive infections caused by S. pyogenes accompanied by sepsis or septic shock, treated at the 4th Clinical Military Hospital in Wroclaw between December 2022 and May 2023. Among 11 patients, 6 had streptococcal skin and soft tissue infections, 3 had pneumonia caused by S. pyogenes, 1 had streptococcal otitis, and 1 had a knee joint infection. Nine developed septic shock, and three died from fulminant streptococcal toxic shock syndrome (STSS). Physicians should be aware of the increased prevalence of invasive GAS (iGAS) infections; timely diagnosis and effective treatment are crucial to reducing the risk of severe complications, including death.